Selected methods of rehabilitation in systemic sclerosis - Agnieszka Gerkowicz; Angelika Bielecka; Justyna Buś; Beata Polkowska-Pruszyńska; Dorota Krasowska (Termedia Publishing House, 2017)
Systemic sclerosis is a chronic connective tissue disease characterized by microvascular abnormalities, immune disturbances and progressive fibrosis of the skin and internal organs. Skin involvement may result in contractures, leading to marked loss of hand mobility, adversely affecting the performance of daily activities and decreasing the quality of life. Face involvement not only causes functional loss, but also lowers the self-esteem of patients. Increasing attention has recently been focused on the need to rehabilitate patients with systemic sclerosis in order to prevent the development of joint contractures and loss of mobility. The study presents a review of the current literature on rehabilitation possibilities in patients with systemic sclerosis, with a special focus on physiotherapy methods.